Profit sharing: Consequences for workers - Tony Fang (IZA World of Labor, 2016)
Profit sharing can lead to higher productivity and thus to higher firm profitability and employee wages. It may also enhance employment stability by enabling firms to adjust wages during downturns rather than lay off workers. While adoption of profit sharing increases earnings fluctuations, it also increases earnings growth in the longer term. As with any group incentive plan, profit sharing may result in some workers benefiting from the effort of others without themselves exerting greater effort (“free-rider problem”). However, there is evidence that in team-based production workplaces, profit sharing may reduce shirking and thus contribute to productivity growth.
Keywords: J33; J38; J32; J24; 330; profit sharing; employee earnings; worker attitudes and behaviors; workplace productivity; employment stability